The bile acid membrane receptor TGR5: a novel pharmacological target in metabolic, inflammatory and neoplastic disorders - Stepanov, V.; Stankov, K.; Mikov, Momir (Informa Healthcare, 2013)
TGR5 is the G-protein–coupled bile acid-activated receptor, found in many human and animal tissues. Considering different endocrine and paracrine functions of bile acids, the current review focuses on the role of TGR5 as a novel pharmacological target in the metabolic syndrome and related disorders, such as diabetes, obesity, atherosclerosis, liver diseases and cancer. TGR5 ligands improve insulin sensitivity and glucose homeostasis through the secretion of incretins. The bile acid/TGR5/cAMP signaling pathway increases energy expenditure in brown adipose tissue and skeletal muscle. Activation of TGR5 in macrophages inhibits production of proinflammatory cytokines and attenuates the development of atherosclerosis. This receptor has been detected in many cell types of the liver where it has anti-inflammatory effects, thus reducing liver steatosis and damage. TGR5 also modulates hepatic microcirculation and fluid secretion in the biliary tree. In cell culture models TGR5 has been linked to signaling pathways involved in metabolism, cell survival, proliferation and apoptosis, which suggest a possible role of TGR5 in cancer development. Despite the fact that TGR5 ligands may represent novel drugs for prevention and treatment of different aspects of the metabolic syndrome, clinical studies are awaited with the perspective that they will complete TGR5 biology and identify efficient and safe TGR5 agonists.